The Emergence of Shi’a Sect as an Implication of the Development of Thought and Politics - Ulvah Nur'aeni (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The emergence of Shi'a sects is a result of the complex interplay between the development of thought and politics within the Shi'a school of Islam. This paper explores the factors that led to the formation of various Shi'a sects throughout history using a descriptive analysis method. The origin and development of Shi'a are discussed, including the diverse opinions regarding its emergence. Some scholars argue that Shi'a existed during the lifetime of Prophet Muhammad, while others believe it formed after his death, during the caliphate of Ali, or after the tragedy of Karbala. The definition of Shi'a is also examined, with four main categories identified: those who believe in Ali's superiority without acknowledging the imamah of other imams; those who prioritize Ali over other companions; those who support Ali and the concept of Imamah; and those who believe in Ali, the infallibility of imams from his lineage, and the necessity to support the imams and oppose their enemies. The development of Shi'a thought and the political landscape played crucial roles in shaping the identity and characteristics of different Shi'a sects. Understanding these factors is essential for gaining a deeper insight into the complex history and diversity within Shi'a Islam, as well as addressing misunderstandings and generalizations about Shi'a beliefs. This paper provides a comprehensive overview of the historical context and interconnected events that contributed to the crystallization of Shi'a as a distinct school of thought and the subsequent emergence of its various sects.